Magnesium and phosphate level during admission in Sepsis patients in relation with mortality and Morbidity in intensive care unit Hospital universiti sains malaysia - Hamid, Azman abd. (2012)
Magnesium And Phosphate Level During Admission In Sepsis Patients In Relation With Mortality And Morbidity In Intensive Care Unit Hospital Universiti Sains Malaysia. Magnesium and phosphate are electrolytes that important for body homeostasis and maintains normal body function. Hypomagnesaemia and hypophosphataemia are frequent phenomenon in hospitalized patient and have a higher prevalence in intensive care. The focus of this study was to determine the prevalence in these both electrolytes in sepsis patient during ICU admission and its relation to mortality and morbidity. The main aim of this study is to determine the level of magnesium and phosphate during ICU admission in sepsis patient admitted to Intensive Care Unit and its relation with mortality and morbidity. This study was a retrospective study with chart review from 108 sepsis adult patients admitted to Intensive Care Unit HUSM from January 2010 to July 2011. The baseline characteristics and ICU outcomes of all patients were retrospectively collected by reviewing their medical record. Patients characteristic including age, sex, APACHE II score, primary reason for ICU, magnesium and phosphate level during admission, ICU stay and last day in ICU were recorded. Total day required for mechanical ventilation, length of ICU stay, ICU mortality and recovery were recorded. There were 52.3% (34/65) ICU mortality from group hypomagnesaemia, 32.3 %( 21/65) normal magnesium and 15.4% (10/65) hypermagnesaemia (p<0.05). There was statistically significant that 53.8 % (21/39) from patients who were discharge home (recovery) have normal magnesium level compare to 35.9% (14/39) hypomagnesaemia. Hypomagnesaemia group required longer ventilatory support with mean 8.06±7.94 days than normal magnesium level group 5.79±6.089 days. The length of ICU stay was longer in hypomagnesaemia group that is 8.88±7.86 days compare with normal magnesium group 7.00±6.863 days (p>0.05). We found that 43.6 % (17/39) from patients who were discharge home (recovery) have normal phosphate level compare to 33.3% (13/39) hypophosphataemia (p>0.05). We also found for hypophosphataemia group required same duration of ventilator support with mean 7.44±6.66 days with normal phosphate level group 7.47±8.70days. The length of ICU stay is similar in hypophosphataemia group that was 8.96±6.41 days and normal phosphate group 8.49±8.64 days. The study was able to determine that the hypomagnesaemia during admission are associated with higher mortality rate and cause more morbidity in term of prolonged ventilatory support and increase length of ICU stay. However hypophosphataemia did not increase mortality and morbidity.